Transformation durch Vermittlung. Das Heilige in der Geschichte pädagogischen und literarischen Wirkens der Jesuiten in Lateinamerika - Freitag, Christine; Thiem, Annegret ((Un)verfügbar - Kulturen des Heiligen)

Vergleichende Perspektive aus dem gleichen Bundesland - ein Kommentar aus Paderborn - Freitag, Christine (Empirische Studien zum Praxissemester: Untersuchungen zum Bielefelder Modell)

Bourdieu and the Quest for Intercultural Transformations - Pöllmann, Andreas (SAGE Open)
Building and expanding on Bourdieu’s notions of cultural capital, habitus, and field, this conceptual article aims to contribute to a better understanding of intercultural transformations. Distancing itself from essentialist reductionism in the analysis of cultures, it associates intercultural transformations with habitus crises through “culture shock,” with the realization of intercultural capital, and with changes in the scope and configuration of cultural pluriformity. In going beyond Bourdieu without abandoning him along the way, the approach outlined in the course of this article combines a range of conceptual tools which may prove to be useful in sustaining struggles for social justice in educational institutions and in society at large.
Keywords: General Social Sciences; General Arts and Humanities

Gesellschaftliche Wirkprozesse des Civic Engagement qualitativ erforschen - Dopheide, F.; Freitag, Christine; Koch, L.; Struchholz, C. (Impulse zu Methoden in der deutschsprachigen Civic Engagement-Forschung)

Denk-Wege zu einer religionssensiblen Schulkultur: erziehungswissenschaftliche Perspektiven - Freitag, Christine (Katechetische Blätter)

Gesellschaftlich Wirkprozesse des Civic Engagement qualitativ erforschen - Freitag, Christine (Impulse zu Methoden in der deutschsprachigen Civic Engagement-Forschung)

Projekt Art-D Grids: Nachhaltige und stabile Microgrids in Afrika - eine Plattform für Forschung und Lehre für die Entwicklung - Krauter, Stefan; Böcker, Joachim; Freitag, Christine; Hehenkamp, Burkhard; Hilleringmann, Ulrich; Temmen, Katrin; Klaus, Tobias; Rohrer, Nicolaus; Lehmann, Sven (Tagungsband des 36. PV-Symposiums, 18.-26 Mai 2021)
Keywords: Art-D; Afrika; Resilienz; Resilience; Grid stability; robustness; microgrids

Transforming study abroad: a handbook - Pöllmann, Andreas (Compare: A Journal of Comparative and International Education)
Keywords: Education

European educational research (re)constructed: institutional change in Germany, the United Kingdom, Norway, and the European Union - Pöllmann, Andreas (Compare: A Journal of Comparative and International Education)
Keywords: Education

Strategies of segregation: race, residence, and the struggle for educational equality - Pöllmann, Andreas (Ethnic and Racial Studies)
Keywords: Sociology and Political Science; Anthropology; Cultural Studies